2006
DOI: 10.3998/ark.5550190.0007.b11
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5-O-benzyl-2-C-β-fluoromethyl-1,2,3-tri-O-acetyl- D-ribofuranose

Abstract: The novel, protected fluoromethylribose (10) was prepared in 7 steps (26% overall yield) from commercially available D-ribonolactone. First, the three hydroxyl groups were protected as the 2,3-isopropylidene-5-benzyl derivative. Reduction of the resulting fully protected ribonolactone to the lactol was achieved by using Cp 2 TiF 2 -catalysed hydrosilylation, followed by hydrolysis. Reaction with formaldehyde installed the 2-C-β-hydroxymethyl group. Treatment with DAST gave the 1-fluoro-2-C-β-fluoromethyl deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In the absence of nanocluster catalysts, no oxidized product was found at 80 °C for 3 days and only starting material 15 was recovered (Table 3, entry 1). Monometallic nanoclusters, 5 mol %, such as Au-PVP, Cu-PVP, and Pd-PVP, were also applied (entries 2−4), and no oxidized product was detected, except in the case of Pd-PVP, where trace amounts of sclaral ( 16) and (+)-sclareolide (17) were isolated (entry 4). The oxidation of 15 proceeded when 5 mol % Pd/Au (3:1)-PVP or Cu/Au (3:1)-PVP was used (entries 5 and 6), albeit only 28% and 33% conversion, respectively.…”
Section: Syntheses Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of nanocluster catalysts, no oxidized product was found at 80 °C for 3 days and only starting material 15 was recovered (Table 3, entry 1). Monometallic nanoclusters, 5 mol %, such as Au-PVP, Cu-PVP, and Pd-PVP, were also applied (entries 2−4), and no oxidized product was detected, except in the case of Pd-PVP, where trace amounts of sclaral ( 16) and (+)-sclareolide (17) were isolated (entry 4). The oxidation of 15 proceeded when 5 mol % Pd/Au (3:1)-PVP or Cu/Au (3:1)-PVP was used (entries 5 and 6), albeit only 28% and 33% conversion, respectively.…”
Section: Syntheses Ofmentioning
confidence: 99%
“…In a comparative study, (+)-sclareolide (17), an oxidation product of (−)-ambroxide (15), has been previously reported in the oxidation with bimetallic nanoclusters Cu/Au/firstgeneration CSPVP. 5a Expectedly, 17, obtained from the oxidation of 15 (see Scheme 4 & Table 3), reacted very slowly with the present catalysts.…”
Section: Syntheses Ofmentioning
confidence: 99%
“…We also evaluated the impact of the protecting groups on the stereochemical outcome of the cyanation reaction by preparing ribonolactone 34 in 3 steps from D-ribose. 17,18 The addition of lithium TIPS-acetylide to lactone 34 yielded hemiketal 35, which gave the desired nitrile 37 in 58% as a single anomer after cyanation and TIPS removal. The stereochemical assignment of the C1′ carbon of 37 revealed that the nitrile group occupied the beta position (see below).…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
“…We also evaluated the impact of the protecting groups on the stereochemical outcome of the cyanation reaction by preparing ribonolactone 34 in 3 steps from d -ribose. 17,18…”
mentioning
confidence: 99%
“…Various concentrations of aqueous TFA, with or without a co-solvent, have been used for 1,2-acetonide deprotections in furanose substrates and, for example, use of a 50% solution was employed for an intransigent fluorinated substrate which, nevertheless, took three days to reach completion. 18 However, application of similar conditions to compounds 15 and 16 gave incomplete reactions, isomerisation at the spiro-centre, and significant decomposition. Fortunately, acceptable deprotections were eventually achieved with an aqueous HF-acetonitrile mixture; 19 although the isolated yields were moderate at best, the final products (2-5, Scheme 4) could be readily isolated and the spiro-centre stereochemistry appeared to be unaffected.…”
mentioning
confidence: 99%